(untitled) (Proceedings of Faculty of Civil Engineering, 2020)
In this paper, the component method for determining the stiffness and bending resistance, which are the basic characteristics of connections, are presented. The application of this method was carried out using the IDEA StatiCa software on the example of the beam-to-column bolted connection with double extended end-plate. The results of the connection behavior were compared to the results obtained by numerical simulation in Abaqus and the results of the behavior obtained by laboratory tests found in references.